Protein adaptations in extremophiles: An insight into extremophilic connection of mycobacterial proteome. (December 2018) - Kumar, Ashutosh; Alam, Anwar; Tripathi, Deeksha; Rani, Mamta; Khatoon, Hafeeza; Pandey, Saurabh; Ehtesham, Nasreen Z.; Hasnain, Seyed E.
Abstract: The biological paradox about how extremophiles persist at extreme ecological conditions throws a fascinating picture of the enormous potential of a single cell to adapt to homeostatic conditions in order to propagate. Unicellular organisms face challenges from both environmental factors and the ecological niche provided by the host tissue. Although the existence of extremophiles and their physiological properties were known for a long time, availability of whole genome sequence has catapulted the study on mechanisms of adaptation and the underlying principles that have enabled these unique organisms to withstand evolutionary and environmental pressures. Comparative genomics has shown that extremophiles possess the unique set of genes and proteins that empower them with biochemical machinery necessary to thrive in extreme environments. The presence of these proteins safeguards the cell against a wide array of extreme conditions such as temperature, pressure, radiations, chemicals, drugs etc. An insight into these adaptive mechanisms in extremophiles may help us to devise strategies to alter the genes and proteins that may have therapeutic potential and commercial value. Here we present an overview of the various adaptations in extremophiles. We also try to explain how mycobacterium channelizes its proteome to survive in stress conditions posed by host immune system.